A ROCK-MAGNETIC RECORD FROM LAKE BAIKAL, SIBERIA: EVIDENCE FOR LATE QUATERNARY CLIMATE CHANGE - Peck J.A.; King J.W.; Colman S.M.; Kravchinsky V.A. (My University, 1994)
Rock-magnetic measurements of sediment cores from the Academician Ridge region of Lake Baikal, Siberia show variations related to Late Quaternary climate change. Based upon the well-dated last glacial-interglacial transition, variations in magnetic concentration and mineralogy are related to glacial-interglacial cycles using a conceptual model. Interglacial intervals are characterized by low magnetic concentrations and a composition that is dominated by low coercivity minerals. Glacial intervals are characterized by high magnetic concentrations and increased amounts of high coercivity minerals. The variation in magnetic concentration is consistent with dilution by diatom opal during the more productive interglacial periods. We also infer an increased contribution of eolian sediment during the colder, windier, and more arid glacial conditions when extensive loess deposits were formed throughout Europe and Asia. Eolian transport is inferred to deliver increased amounts of high coercivity minerals as staining on eolian grains during the glacial intervals. Variations in magnetic concentration and mineralogy of Lake Baikal sediment correlate to the SPECMAP marine oxygen-isotope record. The high degree of correlation between Baikal magnetic concentration/mineralogy and the SPECMAP oxygen-isotope record indicates that Lake Baikal sediment preserves a history of climate change in central Asia for the last 250 ka. This correlation provides a method of estimating the age of sediment beyond the range of the radiocarbon method. Future work must include providing better age control and additional climate proxy data, thereby strengthening the correlation of continental and marine climate records.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная